Analysis of procedural data of pulmonary vein isolation for atrial fibrillation with the second‐generation laser balloon. Issue 7 (29th April 2019) - Nagase, Takahiko; Bordignon, Stefano; Perrotta, Laura; Bologna, Fabrizio; Tsianakas, Nikolaos; Chen, Shaojie; Konstantinou, Athanasios; Chun, Julian K.R.; Schmidt, Boris
Abstract: Background: The procedural data of pulmonary vein (PV) isolation (PVI) for patients with atrial fibrillation using the second‐generation laser balloon (LB2), which became available recently, remains unclear and were evaluated. Methods: Thirty consecutive patients (116 PVs) underwent PVI using LB2 (LB2 group) and were matched to 30 patients (116 PVs) treated with the first‐generation laser balloon (LB1 group). The left atrial isolated surface area (ISA) (ratio of the total isolated antral surface area excluding PV to the total isolated antral surface area including the posterior wall) was also measured after LB2 PVI. Results: PVI was achieved in 103/116 (89%) PVs and 108/116 (93%) PVs in the LB2 and LB1 groups, respectively, after the initial circular ablation (P = 0.360) and in 115/116 (99%) PVs and 116/116 (100%) PVs in the LB2 and LB1 groups, respectively, at the end of the procedure (P = 1.000). PV occlusion grade, categorized by the degree of PV occlusion, was significantly better in the LB2 group than in the LB1 group (P < 0.001). Zero rotational maneuver was applicable in 23/116 (20%) PVs and 8/116 (7%) in the LB2 and LB1 groups, respectively (P = 0.007). There was no significant difference in the procedural time, fluoroscopic time, or complications. The mean ISA after LB2 PVI was 53 ± 14%. The application number was the only independent predictor of successful PVI after initial circular LB2 ablation (adjusted odds ratio 0.860; 95% confidence interval 0.764–0.968; P = 0.013). Conclusion: LB2 displays favorable PV occlusion characteristics and enables more zero rotational maneuvers.